Analysis of Esa Unggul University Students’ Preferences for Leadership Seminars Using Conjoint Analysis - Lili Hastuti; Widiastuti Widiastuti; Muhammad Ichsan; Vera Maya Santi (MASI Mandiri Edukasi, 2026)
This research addresses the need to understand student preferences in leadership seminar design at Esa Unggul University and aims to identify the seminar attributes that most strongly influence participation decisions. A quantitative approach was applied using Conjoint Analysis, involving 100 active students from various study programs who are members of the Student Executive Board (BEM). Data were gathered through structured questionnaires and analyzed to estimate utility scores and relative importance values across five attributes: seminar topic, speaker, delivery format, participation cost, and benefits. The findings show that students favor seminars on Leadership and Entrepreneurship, delivered by expert lecturers, implemented in a hybrid format, priced between IDR 20,000 and 50,000, and offering certificates combined with SKP or competency recognition. Importance value analysis indicates that speaker credibility, cost considerations, and topic relevance are the dominant factors shaping student preferences. Model validation results demonstrate strong predictive accuracy, with a Pearson correlation of 0.815 and Kendall’s tau of 0.407, both statistically significant. These results provide an empirical basis for universities and event organizers to develop leadership seminars that better align with student expectations, thereby improving engagement and program effectiveness.